2021
DOI: 10.1101/2021.11.21.469454
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryo-EM structures of the channelrhodopsin ChRmine in lipid nanodiscs

Abstract: Microbial channelrhodopsins are light-gated ion channels widely used for optogenetic manipulation of neuronal activity. ChRmine is a bacteriorhodopsin-like cation channelrhodopsin (BCCR) more closely related to ion pump rhodopsins than other channelrhodopsins. ChRmine displays unique properties favorable for optogenetics including high light sensitivity, a red-shifted activation spectrum, cation selectivity, and large photocurrents while its slow closing kinetics impede some applications. The structural basis … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…Both Hc KCR1 and 2 form a trimer (Figures 1A and 1B), as was also observed in ChRmine, the only PLCR for which high-resolution structural information is available (Kishi et al, 2022; Tucker et al, 2022). The trimerization is mainly achieved by the direct and lipid-mediated interactions among transmembrane helices (TMs) 1-2 and TMs 4-5 of adjacent protomer, and the center of the trimer interface is filled with six lipid molecules (Figures 1A and 1B).…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Both Hc KCR1 and 2 form a trimer (Figures 1A and 1B), as was also observed in ChRmine, the only PLCR for which high-resolution structural information is available (Kishi et al, 2022; Tucker et al, 2022). The trimerization is mainly achieved by the direct and lipid-mediated interactions among transmembrane helices (TMs) 1-2 and TMs 4-5 of adjacent protomer, and the center of the trimer interface is filled with six lipid molecules (Figures 1A and 1B).…”
Section: Resultssupporting
confidence: 65%
“…The C-terminal TM7 helix is also ∼1.5 turns longer than that of ChRmine (Figure 1F), making it more similar to that of canonical CCRs such as C1C2 (the chimera derived from Cr ChR1 and Cr ChR2) (Figure 1G). In PLCRs, residues from TM1, 2, 3, 7, and ECL1 form the core of the ion-conducting pathway within each monomer (Kishi et al, 2022; Tucker et al, 2022), so the structural differences of TM1, 7, and ECL1 observed in Hc KCRs change the shape of the pathway, to be discussed in more details later.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An inter-protomer conductance has been proposed in ChRmine, based on the cryo-EM structure obtained in detergent (14). However, lipids block the space between the protomers in a ChRmine trimer incorporated in membranous nanodisks (15), which is expected to represent a state of the protein close to that in biological membranes.…”
Section: Discussionmentioning
confidence: 99%
“…KCR protein sequences show the highest homology to cryptophyte BCCRs out of all currently known ChRs (10), although their source organism is phylogenetically very distant from cryptophytes. High-resolution structures of only one BCCR, known as ChRmine, have been reported (14, 15). They show trimeric organization typical of haloarchaeal ion-pumping rhodopsins (16), whereas chlorophyte CCRs and cryptophyte ACRs form dimers (17, 18).…”
Section: Introductionmentioning
confidence: 99%